The urgency of establishing a special agency of personal data protection and supervision to ensure the Indonesian citizens’ privacy rights - Ferina Widyawati Ayu Silvi; Anom Wahyu Asmorojati (Universitas Muhammadiyah Magelang, 2022)
Personal Data Protection is the right of humans, constitutionally the state’s obligation to respect, fulfill, and protect as mandates in Article 28 C paragraph (1) of the 1945 Constitution. However, due to the massive data leaks prove that the rights have not been protected. The research is aimed to know the legal protection for the Indonesian citizens’ personal data by establishing a special agency and intended to find the ideal format of the special agency for personal data protection and supervision to be implemented in Indonesia. The research methods used is the juridical normative through library research. The data were analyzed qualitatively and presented using the descriptive-analysis method. The research is also doctrinal with primary and secondary legal materials. The research concluded that the personal data protection classified as the emerge issues due to the vacuum of law. Moreover, the absence of special agency which plays the important rules to protect or supervise the personal data for the Indonesians. Moreover, its urgency for establishing a special agency for personal data protection and supervision has become the global issues refer to its international regulation and convention, wide conflict of interests in data supervision and management, and due to the occurrence of massive personal data leaks.